2009
DOI: 10.1152/ajpheart.00968.2008
|View full text |Cite
|
Sign up to set email alerts
|

ETAselective receptor antagonism prevents ventricular remodeling in volume-overloaded rats

Abstract: Murray DB, McMillan R, Brower GL, Janicki JS. ETA selective receptor antagonism prevents ventricular remodeling in volume-overloaded rats. Am J Physiol Heart Circ Physiol 297: H109 -H116, 2009. First published May 8, 2009 doi:10.1152/ajpheart.00968.2008.-The objective of this study was to investigate the ability of selective endothelin receptor subtype A (ET A) endothelin receptor antagonism (ETA) to prevent the acute myocardial remodeling process secondary to volume overload. Left ventricular tissue from sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 53 publications
0
10
1
Order By: Relevance
“…However, most studies, exemplified by Levine et al (22), have focused on the positive correlation between end-stage heart failure and elevated circulating levels of TNF-␣. We recently established that myocardial levels of TNF-␣ initially become elevated in the 1st wk after creation of an AV fistula (21,25,26). Accordingly, this study sought to elucidate the contribution of endogenous TNF-␣ at different stages of the remodeling process, using TNF-␣ inhibition with etanercept.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, most studies, exemplified by Levine et al (22), have focused on the positive correlation between end-stage heart failure and elevated circulating levels of TNF-␣. We recently established that myocardial levels of TNF-␣ initially become elevated in the 1st wk after creation of an AV fistula (21,25,26). Accordingly, this study sought to elucidate the contribution of endogenous TNF-␣ at different stages of the remodeling process, using TNF-␣ inhibition with etanercept.…”
Section: Discussionmentioning
confidence: 99%
“…However, a similar pattern of myocardial remodeling consisting of LV wall thinning, dilatation, and collagen degradation was reported by Bozkurt et al (3) following infusion of pathophysiological levels of TNF-␣ in normal rats. The possibility that mast cells initiate collagen degradation and subsequent long-term remodeling by regulating the release of TNF-␣ was raised based upon our recent observation that TNF-␣ is elevated within 24 h after creation of an AV fistula (25,26). That cardiac mast cells contribute to increases in myocardial levels of TNF-␣ is not a novel observation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Norepinephrine and endothelin can up-regulate the activity and expression of MMP-2 [22][23][24][25] . This study found that the expression of MMP-2 was increased in model group as compared with normal group.…”
Section: Discussionmentioning
confidence: 99%